The Role of Systemic Inflammation Response Index for Predicting the Prognosis of Threatened Miscarriage - Gokkaya, Gokce; Vural Yilmaz, Zehra; Yilmaz, Elif (Gynecology Obstetrics & Reproductive Medicine, 2025)
OBJECTIVE: To investigate the value of the systemic inflammation response index (SIRI) in predicting prognosis in pregnant women with abortus imminens (AI). STUDY DESIGN: The study included 203 pregnant women (≤12 weeks) who presented and were hospitalized with AI in our hospital. Eighty-three pregnant women with spontaneous abortions comprised the study group, and 120 women with healthy pregnancies comprised the control group. Demographic and laboratory parameters were obtained from the patients' medical records. SIRI was calculated using the formula: neutrophil count × monocyte count/lymphocyte count. SIRI values were compared between groups. RESULTS: The rate of spontaneous abortion in pregnant women with AI was 40.9% in our study population. The SIRI level was found to be significantly higher in the study group than in the control group (p<0.001). The regression analysis showed that the SIRI level is an independent marker for spontaneous abortion, and it was found that when the SIRI level increases by 1 unit, the risk of abortion increases by 25.4% (OR=1.254, p=0.003). We found that, with a cut-off value of 2.11, SIRI predicted spontaneous abortion with 68.7% sensitivity and 65.8% specificity. CONCLUSION: The SIRI level, a non-invasive, simple, and cheap marker, could be used to assess the spontaneous abortion risk of pregnant women presenting with AI. However, future studies with a larger number of patients and serial measurements of the SIRI level are needed to determine the optimal value for predicting the disease.